ALTMAN Z-SCORE MODEL FOR THE SUSTAINABILITY OF WONG POLO MANGROVE BEACH TOURISM BUSINESS - Hernawaty, Hernawaty; Chrisna, Heriyati; Wahyuni, Sri (Proceeding International Seminar of Islamic Studies, 2023)
This research is focused on analyzing business financial data, which aims to predict business sustainability using the Altman Z-Score method. The data collection technique was carried out using documentation techniques in the form of collecting the required data from existing financial data by the Wong Polo Mangrove Beach Tourism manager from 2019-2021. Data is analyzed using quantitative descriptive analysis. The main target of this research is to analyze financial data to anticipate the condition of financial difficulties (prediction of bankruptcy) using the Altman Z-Score method so that planned corrective actions can be taken for the sustainability of Wong Polo Mangrove Beach Tourism business and can be a reference for other tourist attractions in Kota Pari Village. In the planned improvement efforts, cooperation is needed from business owners, local governments, and communities around tourist sites.